Safety of Botulinum Toxin A in Aesthetic Treatments: A Systematic Review of Clinical Studies. Issue 5 (28th February 2014) - Cavallini, Maurizio; Cirillo, Pierfrancesco; Fundarò, Salvatore Piero; Quartucci, Sandro; Sciuto, Chantal; Sito, Giuseppe; Tonini, Davide; Trocchi, Gloria; Signorini, Massimo
<x xml:space="preserve">Abstract</x> Background The use of botulinum toxin A (BoNT‐A) for aesthetic treatments is growing steadily, and new safety data have been reported in recently published studies. Objective To investigate the safety data on the use of the three BoNT‐A formulations approved for facial aesthetics from recent studies and to confirm their safety profiles. Methods The literature search was conducted using three online databases restricted to the timeframe from January 2000 to June 2012. Only clinical trials, randomized or open label, with safety as the primary or secondary endpoint, were included. Results Thirty‐five papers were selected, with a total of subjects 8, 787 studied. OnabotulinumtoxinA was used in 60.0% of the studies, abobotulinumtoxinA in 37.1%, and incobotulinumtoxinA in 2.8%. The glabella was the most investigated area (51.4%), followed by the upper face (25.7%), crow's feet (11.4%), and lower face (11.4%). Treatment‐related adverse events were blepharoptosis (2.5%), brow ptosis (3.1%), and eye sensory disorders (3%) in the upper face and lip asymmetries and imbalances in the lower face (6.9%). All of these events resolved spontaneously. Conclusion The short‐term safety profile of BoNT‐A in cosmetic nonsurgical procedures was confirmed for all the three commercial formulations.